Law, violence, and the possibility of justice - Sarat, Austin (Princeton : Princeton University Press, 2001)
Law punishes violence, yet law depends on violence. In this book, a group of leading interdisciplinary legal scholars seeks to map the inexorable but unstable relationship of law to violence. What does it mean to talk about the violence of law? Do high incarceration rates and increased reliance on capital punishment indicate that U.S. law is growing more violent at a time when violence is being restrained in other legal systems? How is the violence of law represented in popular culture and does this affect law's actual legitimacy? Does violence express or distort the essence of law? Does law's violence serve justice? In deeply original essays, the authors build on the seminal work of Robert Cover--one of the few legal scholars ever to consider the question of law and violence. In striving to situate his insights within current political, social, economic, and cultural contexts, they contemplate diverse and interrelated subjects surrounding the theme of law and violence. Among these are the purpose of law as punishment, the increasing number of executions in the United States, prison violence, racial disparity in sentencing, and the meaning of torture. The result is a remarkable volume that stimulates us to reconsider connections that we too often leave unexplored. In addition to the editor, the contributors are Marianne Constable, Peter Fitzpatrick, Thomas R. Kearns, Peter Rush, Jonathan Simon, Shaun McVeigh, and Alison Young.
Ch. One. Situating law between the realities of violence and the claims of justice: an introduction / Austin Sarat -- Ch. Two Vicissitudes of law's violence / Jonathan Simon -- Ch. Three. Making peace with violence: Robert Cover on law and legal theory / Austin Sarat, Thomas R. Kearns -- Ch. Four. Silence of the law: justice in Cover's "field of pain and death" / Marianne Constable -- Ch. Five. Judgment dwelling in law: violence and the relations of legal thought / Shaun McVeigh, Peter Rush, Alison Young -- Ch. Six. Why the law is also nonviolent / Peter Fitzpatrick.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Law -- Philosophy; Violence (Law); Justice; Violence -- Droit; Justice; Justice; Law -- Philosophy; Violence (Law); Gewalt; Rechtsphilosophie; Aufsatzsammlung; Wetgeving; Geweld